“Come and show me your look”, interview with the artist teacher Mapige (Revista Apotheke, 2024)
It refers to an interview with the artist professor Maria Pinho Gemaque. Known as Mapige, the visual-activist artist, from the north, works with creative processes in visual poetics, performance, drawing, collages, photography, urban intervention, video art, artistic installation, artist's book, film.doc, cultural production, exhibition curation, exchange and artistic experience. Weaving a dialogue between art and the teaching artist, I explore Mapige's processes of creation, artistic intervention, performances and artistic actions with the aim of expanding reflection on contemporary art, aesthetic experience and teaching. I propose to think about artistic practice from its pedagogical, political and discursive dimension that is reflected in Mapige's work. Using netnography methodological processes, the interview was carried out via the social network WhatsApp, in December 2021 due to the distancing effects of the Covid-19 pandemic and the flu outbreak. The result of the interview was an inspiring conversation, full of curiosities and discoveries about the artist's life, creative process and work.
Keywords: contemporary art; teaching artist; aesthetic experience